AB0716 An autopsy case of systemic sclerosis with severe intestinal involvement and literature review. (12th June 2018) - Aoki, A.; Hirano, H.; Kobayashi, H.; Okubo, T.; Umebayashi, Y.; Oka, H.
Abstract : Background: The gastrointestinal tract (GIT) is the second most common internal organ affected by systemic sclerosis (SSc). The rate of SSc patients who develop severe GIT symptoms is lower than 10%, although various degrees of chronic intestinal pseudo-obstruction (CIPO) may occur in as many as 40% of cases (1.2). Objectives: To report an autopsy case of SSc with severe intestinal involvement and review the associated literature. Methods: We will present the clinical features and autopsy findings of a SSc patient and literature concerning Japanese SSc autopsy cases associated with severe intestinal involvement, found Igaku-chuo and Pub-med on Internet. Results: A 69-year-old Japanese woman was diagnosed with diffuse cutaneous SSc from skin sclerosis, Raynaud's phenomenon, and mild interstitial pneumonia in January 2013. The antinuclear antibody was positive (1:160, speckled pattern), but the specific antibodies, including the anti-RNP, topoisomerase I, and centromere antibodies, were negative. In August 2015, at the age of 71, she was hospitalised for vomiting and abdominal pain. Plain abdominal radiograph showed dilation of the small bowel with air-fluid levels. Abdominal CT revealed large dilation of the small bowel in the absence of any mechanical obstruction. These findings were consistent with CIPO. Her symptoms soon improved by decompression with a long intestinal tube. But she experienced frequent relapse of CIPO. During the third hospitalisation in May 2016, an abdominal CT showed pneumatosis cystoides intestinalis (PCI) and free air in the peritoneal cavity. Medical management failed to control the CIPO. Her general conditions had gradually worsened with weight loss of 10 kg in 3 years. Home parental nutrition was initiated in January 2017. On May 2017, she developed severe pneumonia after vomiting, and her condition gradually deteriorated. She finally succumbed to her illness and an autopsy was performed. The whole alimentary tract except for the duodenum showed a thinning of the lamina propria and atrophy of the smooth muscular layers. Intimal proliferation and narrowing of arterioles were also noted. There was non-specific interstitial pneumonitis in the both lower lobes and diffuse alveolar damage in the both of upper lobes of the lungs. Vasculopathy was also seen in the lungs and heart. The cases in the literature are summarised in table 1. Vascular damage and/or smooth muscle atrophy were presented in all cases. M, male; F, female; yr, years; mo, months; GIT, gastrointestinal tract; IP, interstitial pneumonia; CIPO, chronic intestinal pseudo-obstruction; PCI, pneumatosis cystoides intestinalis; 1) Intimal proliferation and narrowing of the small arteries Conclusions: Vasculopathy in SSc involves small vessels, and it precedes fibrosis. 3 The triggering event of vasculopathy is unknown, but the narrowing of intestinal arterioles causing hypoxia might be responsible for dysmotility of GIT. References: [1] Sjogren RW. Gastrointestinal motility disorders in scleroderma. Arthritis Rheum1994; 37:1265–82. [2] MacMahan ZH, et al. Determining the risk factors and clinical features associated with severe gastrointestinal dysmotility in systemic sclerosis. Arthritis Care Res2017Nov 28 [3] Gabrielli A, et al. Mechanisms of disease Scleroderma. New Engl J Med2009; 360: 1989–2003. Disclosure of Interest: None declared